Vegetation shift from deciduous to evergreen dwarf shrubs in response to selective herbivory offsets carbon losses: evidence from 19years of warming and simulated herbivory in the subarctic tundra - Ylänne, Henni; Stark, Sari; Tolvanen, Anne
Selective herbivory of palatable plant species provides a competitive advantage for unpalatable plant species, which often have slow growth rates and produce slowly decomposable litter. We hypothesized that through a shift in the vegetation community from palatable, deciduous dwarf shrubs to unpalatable, evergreen dwarf shrubs, selective herbivory may counteract the increased shrub abundance that is otherwise found in tundra ecosystems, in turn interacting with the responses of ecosystem carbon (C) stocks and CO2 balance to climatic warming. We tested this hypothesis in a 19-year field experiment with factorial treatments of warming and simulated herbivory on the dominant deciduous dwarf shrub Vacciniummyrtillus. Warming was associated with a significantly increased vegetation abundance, with the strongest effect on deciduous dwarf shrubs, resulting in greater rates of both gross ecosystem production (GEP) and ecosystem respiration (ER) as well as increased C stocks. Simulated herbivory increased the abundance of evergreen dwarf shrubs, most importantly Empetrum nigrum ssp. hermaphroditum, which led to a recent shift in the dominant vegetation from deciduous to evergreen dwarf shrubs. Simulated herbivory caused no effect on GEP and ER or the total ecosystem C stocks, indicating that the vegetation shift counteracted the herbivore-induced C loss from the system. A larger proportion of the total ecosystem C stock was found aboveground, rather than belowground, in plots treated with simulated herbivory. We conclude that by providing a competitive advantage to unpalatable plant species with slow growth rates and long life spans, selective herbivory may promote aboveground C stocks in a warming tundra ecosystem and, through this mechanism, counteract C losses that result from plant biomass consumption. 2015